Titanium carbonitride-based metal ceramic material, preparation method thereof, and application in heat sink for glass precision molding

By using titanium carbonitride-based metal cermet materials with nickel-cobalt metal bonding phase, zirconia diffused phase and silicon nitride whisker-strengthening phase, the existing heat-hospital plates have poor oxidation resistance, poor dimensional stability and thermal shock resistance. The problem of poor performance has achieved efficient glass precision molding production.

CN116497254BActive Publication Date: 2025-02-18CHANGSHA SHARPEN ADVANCED MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310529295.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-11
Publication Date
2025-02-18
Estimated Expiration
2043-05-11

AI Technical Summary

Technical Problem

The coated carbide heat-stained plates used in existing glass precision molding molds have poor oxidation resistance, poor dimensional stability, low life, and poor thermal shock resistance and easy cracking.

Method used

Using titanium nitride-based metal cermet materials containing nickel-cobalt metal bonding phase, zirconia diffused phase and silicon nitride whisker-strengthening phase, it is prepared by powder metallurgy method, combined with high-energy ball milling, ball milling mixing and electroless nickel plating. , improve the material's oxidation resistance, thermal shock resistance and high temperature dimensional stability.

Benefits of technology

It realizes the high oxidation resistance, dimensional stability and thermal shock resistance of titanium nitride-based metal cermet materials, extends the service life of the heat-efficient plate, and improves the accuracy and production efficiency of glass precision molding.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a titanium carbonitride-based metal ceramic material and a preparation method thereof and an application thereof in a heat soaking plate for precision glass molding, belonging to the technical field of metal ceramic materials. The titanium carbonitride-based metal ceramic material comprises a nickel-cobalt metal bonding phase, a zirconium oxide dispersion phase and a silicon nitride whisker reinforcement phase; the ... 2 C, TaC and / or NbC, Zr, carbon black, NbN and / or AlN, Si 3 N 4 Powder raw materials including whiskers, Co and Ni are obtained by powder metallurgy method. They have excellent antioxidant properties, high temperature dimensional stability and high thermal shock resistance. Processing them into heat spreaders can improve the accuracy and stability of glass precision molding and the service life of the heat spreader, thereby reducing production costs and providing higher production efficiency and production stability for glass hot bending.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a metal ceramic material, in particular to a metal ceramic soaking plate for high thermal shock resistance curved glass precision molding and a preparation method thereof, belonging to the technical field of metal ceramic materials. Background Art

[0002] Glass precision molding technology is used to prepare complex-shaped glass windows such as 3D curved glass and aspherical curved glass for mobile phones. It has the advantages of high production efficiency, short production process and low production cost. Therefore, it is the key technology for mass production of complex curved glass in the current industry. With the rapid development of data, information and intelligent technology, the requirements for windows are getting higher and higher. Therefore, high efficiency puts forward extremely high requirements for the dimensional accuracy and light transmittance of glass, and thus the precision requirements for glass molding technology are also rapidly increasing. In the production and application of curved glass, aspherical curved glass is widely used as a lens in security, monitoring and automotive automatic driving industries that require imaging. The collected image information directly determines the accuracy of the final output result. Therefore, the precision requirements for aspherical curved glass are higher than those for other curved glass. Most of the dimensional accuracy requirements are within 0.3 microns, so the precision of the precision molding technology of aspherical curved glass is also higher.

[0003] The difficulty and precision requirements of precision molding of aspheric curved glass are much higher than those of 3D curved glass. In addition, since the mold used is a non-bonded carbide mold with huge density and weight, it needs to absorb a large amount of heat during the precision molding process. Therefore, the heat spreader that is in direct contact with the mold has higher requirements on thermal shock resistance, temperature uniformity, thermal conductivity and oxidation resistance.

[0004] At present, WC-based cemented carbide coating is often used in precision glass molding in industrial applications, but its poor oxidation resistance and thin coating thickness, as well as the complex shape of the heat spreader design, make it difficult for the coating to be completely covered, resulting in a limited life of the heat spreader, and its own flatness is prone to change, and it is easy to produce yellow tungsten oxide powder, which pollutes the mold and the product. Titanium carbonitride-based metal ceramics have excellent oxidation resistance and high-temperature hardness, and can maintain dimensional stability during long-term use, but their thermal shock resistance is poor. In the production of aspherical glass, the heat is frequently absorbed rapidly by the mold, and titanium carbonitride-based metal ceramics will crack. In summary, it is urgent to develop a metal ceramic material heat spreader that can not only ensure excellent dimensional accuracy and oxidation resistance, but also has high thermal shock resistance. Summary of the invention

[0005] In view of the technical problems that the coated carbide heat spreaders used in existing glass precision molding molds have poor oxidation resistance, poor dimensional stability, and short service life, and the metal ceramic heat spreaders have poor thermal shock resistance and are easy to crack, the first purpose of the present invention is to provide a titanium carbonitride-based metal ceramic material that has excellent oxidation resistance and high temperature dimensional stability as well as high thermal shock resistance, which is particularly suitable for preparing metal ceramic heat spreaders.

[0006] The second object of the present invention is to provide a method for preparing a titanium carbonitride-based metal ceramic material, which is simple to operate, low in cost and conducive to large-scale production.

[0007] The third object of the present invention is to provide an application of a titanium carbonitride-based metal ceramic material, which has excellent oxidation resistance, high-temperature dimensional stability and high thermal shock resistance. Processing it into a metal ceramic heat spreader can improve the accuracy and stability of glass precision molding and the life of the heat spreader, thereby achieving the purpose of reducing production costs and providing higher production efficiency and production stability for glass hot bending.

[0008] In order to achieve the above technical objectives, the present invention provides a titanium carbonitride-based metal ceramic material, which contains a nickel-cobalt metal bonding phase, a zirconium oxide dispersed phase and a silicon nitride whisker strengthening phase; the titanium carbonitride-based metal ceramic material is obtained by a powder metallurgy method from powder raw materials including Ti(C, N), WC, Mo2C, TaC and / or NbC, Zr, carbon black, NbN and / or AlN, Si3N4 whiskers, Co, and Ni.

[0009] The titanium carbonitride-based metal ceramic material of the present invention is prepared by a powder metallurgy method using Ti(C, N), WC, Mo2C, TaC and / or NbC, Zr, carbon black, NbN and / or AlN, Si3N4 whiskers, Co, Ni and other main raw materials. It has excellent oxidation resistance and high-temperature dimensional stability as well as high thermal shock resistance. It mainly adopts a high-toughness and oxidation-resistant nickel-cobalt metal bonding phase to provide high toughness and strength, and uses metal nitrides such as NbN and AlN to compensate for the denitrification problem and high-temperature strength reduction problem caused by the high bonding phase content. The thermal shock resistance is improved by using zirconium oxide dispersion strengthening and the introduction of silicon nitride whiskers. Therefore, while ensuring that the titanium carbonitride-based metal ceramic material has high-temperature hardness, strength and oxidation resistance, the thermal shock resistance is also significantly improved.

[0010] As a preferred solution, the raw materials include the following mass percentage components: WC 15-20%; Mo2C 5-8%; TaC and / or NbC 1-3%; Ni and Co 20-25%; NbN and / or AlN 0.2-1.0%; Si3N4 whisker 0.5-1.0%; Zr 1.0-3.0%; carbon black 0.4-1.0%; the balance is Ti(C,N), and the total mass is 100%. Among the raw materials, Ti(C,N), WC, and Mo2C are the basic raw materials commonly used in titanium carbonitride-based cermet materials. These basic raw materials can ensure that the materials have good strength and toughness. The introduction of TaC and / or NbC can improve the high-temperature strength and high-temperature hardness of the materials. As metal binder phases, the proportion of Co and Ni components is higher than that of conventional cermet materials, which can further enhance the toughness and strength of the materials. The introduction of nitrides such as NbN and AlN will decompose during high-temperature sintering. On the one hand, it produces a high nitrogen potential to compensate for the removal of nitrogen caused by the high binder phase content. On the other hand, the alloy elements produced after decomposition can combine with the binder phase cobalt and nickel to produce fine intermetallic compounds, which strengthen the high-temperature strength of the binder phase while improving the oxidation resistance. It is further preferred that the mass ratio of cobalt and nickel is (3-5): (5-7). The preferred nickel-cobalt ratio makes the binder phase have higher toughness and oxidation resistance.

[0011] As a preferred solution, the particle size of the Ti(C,N) is 4 to 6 μm.

[0012] As a preferred solution, the particle sizes of WC, Mo2C, TaC, NbC, Zr, carbon black, NbN, AlN, Co and Ni are all 3 to 8 μm. Selecting a finer particle size is beneficial to improving sintering activity and distribution uniformity, but too fine a particle size will also lead to ball milling drying oxidation and heating, so a suitable particle size range is selected.

[0013] As a preferred solution, the diameter of the silicon nitride whisker is 0.5-1.0 μm and the length is 20-50 μm. If the whisker is too thick or too long, it will have poor wettability with the substrate and insufficient bonding strength, which will become the source of defects in the failure process, thereby reducing strength. If the whisker is too thin or too short, it will lead to insufficient strengthening effect and it will be difficult to improve strength and thermal conductivity.

[0014] The present invention also provides a method for preparing a titanium carbonitride-based metal ceramic material, which comprises the following steps:

[0015] 1) cleaning and nickel-plating the surface of Si3N4 whiskers to obtain nickel-plated Si3N4 whiskers;

[0016] 2) carbon-oxidizing powders including Zr, carbon black, Co and Ni by high-energy ball milling, and then mixing with NbN and / or AlN powders by ball milling I to obtain mixed powder I, mixing mixed powder I with powders including Ti(C, N), WC, Mo2C and TaC and / or NbC by ball milling II to obtain mixed powder II, mixing mixed powder II with nickel-plated Si3N4 whiskers by ball milling III, and drying to obtain mixed powder III;

[0017] 3) The mixed powder III is pressed and sintered to obtain a titanium carbonitride-based metal ceramic material.

[0018] As a preferred solution, the nickel particles in the nickel coating on the surface of the nickel-plated Si3N4 whiskers have a particle size of less than 100 nm and a thickness of 300 to 500 nm. Nickel plating on the surface of the Si3N4 whiskers is beneficial to improving the bonding strength between the whiskers and the substrate, thereby improving the material strength.

[0019] As a preferred solution, the conditions of the high-energy ball milling are: dry ball milling, ball milling speed of 400-500r / min, ball-to-material ratio of (10-15):1, ball milling time of 2-4h, and ball milling atmosphere of an inert atmosphere with an oxygen content of less than 2vol.%. The purpose of high-energy reactive ball milling carbon oxidation is to form finely dispersed zirconium oxide and zirconium carbide in the metal phase. The presence of zirconium carbide can inhibit grain growth, and the presence of zirconium oxide can absorb thermal stress through phase change during working conditions to improve the thermal shock resistance of the material.

[0020] As a preferred solution, the conditions of the ball milling mixing I are: wet ball milling, alcohol as the ball milling medium, a ball milling speed of (150-200) r / min, a ball-to-material ratio of (3-6):1, and a ball milling time of 24-48 hours. The purpose of the ball milling mixing I is to uniformly mix the binder phase and the binder phase reinforcement phase to prevent the inability to disperse uniformly during the subsequent low-intensity ball milling process.

[0021] As a preferred solution, the conditions of the ball milling mixing II are: wet ball milling, the ball milling medium is alcohol, the ball milling speed is (150-200) r / min, the ball-to-material ratio is (3-6):1, and the ball milling time is 24-48h.

[0022] As a preferred solution, the conditions of the ball milling mixing III are: wet ball milling, the ball milling method is planetary ball milling or drum ball milling; when planetary ball milling is used, the ball milling medium is alcohol, the ball milling speed is (100-120) r / min, the ball-to-material ratio is (1-2):1, and the ball milling time is 3-6 hours; when drum ball milling is used, the ball milling speed is (50-80) r / min, and the ball milling time is 6-12 hours. Drum ball milling is preferred, which has the advantage of large discharge volume. Ball milling mixing III uses low-intensity ball milling, which can ensure uniform mixing of components while not destroying the coating and structure of the Si3N4 whisker itself, ensuring high bonding strength and higher strengthening effect in subsequent sintering.

[0023] As a preferred solution, the compression molding adopts die pressing or cold isostatic pressing, and the compression molding pressure is 150-200 MPa.

[0024] As a preferred solution, the sintering adopts vacuum-gas pressure sintering, and the temperature is raised by program, the heating rate is 5-10°C / min, and the vacuum sintering is first performed to 1200°C, and the vacuum sintering gas pressure is 0.01-1Pa; after 1200°C, it is switched to gas pressure sintering, the gas pressure sintering pressure is 5-11MPa, the maximum sintering temperature is 1450°C-1550°C, and the holding time is 1-3h. During the sintering process, before the sintering temperature is 1200°C, one or more sintering platforms can also be included, for example, the sintering platforms are 120°C, 400°C, 800°C, 1000°C, and the holding time is 60-90min. The vacuum sintering stage is mainly for degreasing and degassing, and gas pressure sintering is used after 1200°C, on the one hand to increase the pressure to inhibit the sintering and denitrification of titanium carbonitride, and on the other hand to further improve the material density by pressurization.

[0025] The present invention also provides an application of a titanium carbonitride-based metal ceramic material, which is used to prepare a heat soaking plate for precision molding of glass. In particular, a metal ceramic heat soaking plate for precision molding of aspherical curved glass. Based on the excellent oxidation resistance and high temperature hardness of the metal ceramic material, it can maintain dimensional stability during long-term use, and has good thermal shock resistance. In the production of aspherical glass, it will not crack due to frequent and rapid absorption of heat.

[0026] The method for preparing a titanium carbonitride-based metal ceramic soaking plate provided by the present invention comprises the following steps:

[0027] (1) Pretreatment of Si3N4 whiskers: After degreasing and cleaning, a nickel coating is plated on the surface of the Si3N4 whiskers by chemical plating. The nickel particles in the nickel coating have a size of less than 100 nm and the nickel coating thickness is 300-500 nm. Chemical plating adopts a common method in the prior art, such as dispersing the Si3N4 whiskers on an ultrasonic disperser, adding the dispersed whiskers into a prepared chemical plating solution for chemical plating. The main components of the plating solution are nickel sulfate (30 g / L), sodium hypophosphite (30 g / L) and sodium citrate (10 g / L). The plating solution is weakly acidic. The plating time is 2-4 minutes, and the time is selected according to the required nickel coating thickness.

[0028] (2) Powder premixing: The metal binder phase (Co and Ni) and Zr and C are carbon-oxidized by high-energy ball milling. The high-energy reaction ball milling method is dry milling. The ball milling speed is 400-500 r / min, the ball-to-material ratio is (10-15):1, the ball milling time is 2-4 h, and the ball milling atmosphere is argon atmosphere with an oxygen content of less than 2 vol.%. After high-energy ball milling, they are premixed with nitride powders such as NbN and / or AlN by ordinary ball milling. The ordinary ball milling premixing method is wet milling. The ball milling medium is alcohol. The ball milling speed is (150-200) r / min, the ball-to-material ratio is (3-6):1, and the ball milling time is 24-48 h to obtain a binder phase premixed powder.

[0029] (3) Mixing of raw material powders: The premixed powder of binder phase, Ti(C, N), WC, Mo2C, TaC and / or NbC, and molding agent (such as paraffin, rubber, PEG, etc., added in an amount of 0.3-0.6% of the total mass of the powder) are mixed by ordinary ball milling. The mixing method is wet milling, the ball milling medium is alcohol, the ball milling speed is (150-200) r / min, the ball-to-material ratio is (3-6):1, the ball milling time is 24-48 h, and then the surface nickel plating is added. The Si3N4 whiskers are continued to be mixed by low-intensity ball milling. The low-intensity ball milling adopts wet ball milling. The ball milling medium is alcohol. The ball-to-material ratio is (1-2):1. The low-intensity ball milling method can adopt commonly used planetary ball milling or drum ball milling. When planetary ball milling is adopted, the ball milling speed is (100-120) r / min and the grinding time is 3-6h. When drum ball milling is adopted, the ball milling speed is (50-80) r / min and the ball milling time is 6-12h. The mixed material is obtained after drying.

[0030] (4) Pressing and sintering: The mixture is pressed and formed under certain conditions. The pressing can be die pressing or cold isostatic pressing. The pressing pressure is 150-200 MPa to obtain a pressed blank. The pressed blank is placed in a sintering furnace for sintering. The sintering adopts a vacuum-gas pressure sintering method. The temperature is raised by program at a rate of 5-10 °C / min. The mixture is vacuum sintered to 1200 °C and the vacuum sintering pressure is 0.01-1 Pa. After 1200 °C, the mixture is switched to gas pressure sintering. The gas pressure sintering pressure is 5-11 MPa, the maximum sintering temperature is 1450-1550 °C, and the holding time is 1-3 h. After the high-temperature sintering is completed, the mixture is cooled to obtain a titanium carbonitride-based metal ceramic material.

[0031] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0032] 1. The titanium carbonitride-based metal ceramic material of the present invention adopts a higher content of tough, oxidation-resistant nickel-cobalt metal binder phase, which gives the titanium carbonitride-based metal ceramic material higher thermal conductivity, strength and toughness. In the actual application process as a heat spreader material, it can provide higher resistance to crack generation and expansion during the rapid heat absorption of the mold, thereby improving the thermal shock resistance of the material.

[0033] 2. The titanium carbonitride-based metal ceramic material of the present invention is based on the fact that the use of a higher metal bonding phase will bring about the problem of sintering denitrification and the reduction of high-temperature strength. By adding alloy element nitrides, decomposition during high-temperature sintering can be used to supplement nitrogen during sintering. At the same time, the alloy elements can form intermetallic compounds with cobalt and nickel to strengthen the metal bonding phase and improve its high-temperature strength.

[0034] 3. The titanium carbonitride-based metal ceramic material of the present invention improves the thermal conductivity of the material by adding silicon nitride whiskers. At the same time, the pull-out and connection effects of the whiskers can inhibit the generation and growth of cracks and improve the thermal shock resistance of the material. At the same time, the bonding phase contains dispersed zirconium oxide, which can change the phase volume through phase change during rapid temperature changes, thereby reducing thermal stress and avoiding cracking.

[0035] 4. The preparation method of the titanium carbonitride-based metal ceramic material of the present invention is simple to operate, low in cost, and is conducive to large-scale production.

[0036] 5. The titanium carbonitride-based metal ceramic material of the present invention has excellent antioxidant properties, high-temperature dimensional stability and high thermal shock resistance. It can be used to prepare titanium carbonitride-based metal ceramic heat spreaders, which can improve the accuracy and stability of glass precision molding and the life of the heat spreader, thereby achieving the purpose of reducing production costs and providing higher production efficiency and production stability for glass hot bending. DETAILED DESCRIPTION

[0037] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.

[0038] Performance test: Flexural strength standard GB / T 3851-2015.

[0039] Fracture toughness standard GB / T 33819-2017.

[0040] Strength after quenching at 700℃: Heat the material to 700℃ in an argon protective atmosphere and keep it warm for 10 minutes, then quench it with water as the medium. After quenching, test the strength according to the bending strength standard GB / T 3851-2015.

[0041] Oxidation weight gain per unit area at 800℃ within 10h: in accordance with standard GB / T 13303-1991.

[0042] In the following specific examples, the average particle size of Ti(C,N) is 5 μm;

[0043] The particle size of powder raw materials such as WC, Mo2C, TaC, NbC, Zr, carbon black, NbN, AlN, Co and Ni is 4μm;

[0044] The diameter of the silicon nitride whisker is 0.5 to 1.0 μm, and the length is 20 to 50 μm.

[0045] Method for chemical nickel plating on the surface of silicon nitride whiskers: disperse Si3N4 whiskers on an ultrasonic disperser, add the dispersed whiskers into the prepared chemical plating solution for chemical plating. The main components of the plating solution are nickel sulfate (30g / L), sodium hypophosphite (30g / L) and sodium citrate (10g / L). The plating solution is weakly acidic and the plating time is determined according to the thickness.

[0046] Example 1

[0047] Raw materials: WC 15%; Mo2C 5%; NbC 1%; nickel and cobalt 20% (nickel-cobalt mass ratio 7:3); NbN 0.2%; Si3N4 whisker 0.5%; Zr 1.0%; carbon black 0.7%; the balance is Ti (C, N), measured based on the total mass as 100%.

[0048] (1) Si3N4 whisker pretreatment: After degreasing and cleaning pretreatment, a nickel coating is plated on the surface of the Si3N4 whisker by chemical plating. The nickel particles in the nickel coating have a particle size of 60 to 80 nm and a nickel plating thickness of about 400 nm.

[0049] (2) Powder premixing: The metal binder phase (Co and Ni) and Zr and C are carbon oxidized by high-energy ball milling. The high-energy reaction ball milling method is dry milling. The ball milling speed is 400 r / min, the ball-to-material ratio is 10:1, the ball milling time is 4 h, and the ball milling atmosphere is argon atmosphere with an oxygen content of 1.5 vol.%. After high-energy ball milling, they are premixed with NbN nitride powder by ordinary ball milling. The ordinary ball milling premixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 150 r / min, the ball-to-material ratio is 3:1, and the ball milling time is 24 h to obtain a binder phase premixed powder.

[0050] (3) Mixing of raw material powders: The binder phase premixed powder, Ti(C,N), WC, Mo2C, NbC and a molding agent (paraffin, added in an amount of 0.4% of the total mass of the powder) are mixed by ordinary ball milling. The mixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 200 r / min, the ball-to-material ratio is 3:1, and the ball milling time is 24 h. Then, Si3N4 whiskers with nickel plating on the surface are added and continued to be mixed by low-intensity ball milling. The low-intensity ball milling adopts a planetary ball milling method. The ball milling medium is alcohol. Wet ball milling is adopted. The ball milling speed is 120 r / min, the material ratio is 2:1, and the milling time is 3 h. The mixed material is obtained after drying.

[0051] (4) Pressing and sintering: The mixture is pressed under certain conditions. The pressing adopts die pressing with a pressing pressure of 150 MPa to obtain a pressed blank. The pressed blank is placed in a sintering furnace for sintering. The sintering adopts a vacuum-gas pressure sintering method. The temperature is raised by programmed sintering with a heating rate of 5 °C / min. The mixture is vacuum sintered to 1200 °C with a vacuum sintering pressure of 0.8 Pa. After 1200 °C, it is switched to gas pressure sintering with a gas pressure sintering pressure of 5 MPa, a maximum sintering temperature of 1550 °C, and a holding time of 2 h. After high-temperature sintering, the mixture is cooled to obtain a titanium carbonitride-based metal ceramic material.

[0052] Performance test results: flexural strength is 2200MPa, fracture toughness is 11MPa·m 1 / 2 After quenching at 700℃, the strength is 1750MPa, and the unit area oxidation weight gain is 9×10 -4 mg / mm 2 .

[0053] Example 2

[0054] Raw materials: WC 17%; Mo2C 6%; TaC 1.5%; nickel and cobalt 22% (nickel-cobalt mass ratio 5:5); AlN 0.5%; Si3N4 whisker 0.7%; Zr 1.5%; carbon black 0.5%; the balance is Ti (C, N), measured based on the total mass as 100%.

[0055] (1) Si3N4 whisker pretreatment: After degreasing and cleaning pretreatment, a nickel coating is plated on the surface of the Si3N4 whisker by chemical plating. The nickel particles in the nickel coating have a size range of 40 to 60 nm and a nickel plating thickness of about 320 nm.

[0056] (2) Powder premixing: The metal binder phase (Co and Ni) and Zr and C are carbon oxidized by high-energy ball milling. The high-energy reaction ball milling method is dry milling. The ball milling speed is 500 r / min, the ball-to-material ratio is 15:1, the ball milling time is 4 h, and the ball milling atmosphere is argon atmosphere with an oxygen content of 1.5 vol%. After high-energy ball milling, they are premixed with AlN nitride powder by ordinary ball milling. The ordinary ball milling premixing method is wet milling. The ball milling medium is alcohol. The ball milling speed is 200 r / min, the ball-to-material ratio is 6:1, and the ball milling time is 48 h to obtain a binder phase premixed powder.

[0057] (3) Mixing of raw powders: The premixed powder of the binder phase, Ti(C,N), WC, Mo2C, TaC, and a molding agent (paraffin wax, added in an amount of 0.4% of the total mass of the powder) are mixed by ordinary ball milling. The mixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 150 r / min, the material ratio is 6:1, and the ball milling time is 24 h. Then, Si3N4 whiskers with nickel plating on the surface are added and continued to be mixed by low-intensity ball milling. The low-intensity ball milling adopts wet ball milling. The ball milling medium is alcohol (industrial anhydrous ethanol). Roller ball milling is used. The material ratio is 1:1, the ball milling speed is 50 r / min, and the milling time is 6 h. The mixed material is obtained after drying.

[0058] (4) Pressing and sintering: The mixture is pressed and formed under certain conditions. The pressing method is mold pressing. The pressing pressure is 200 MPa to obtain a pressed blank. The pressed blank is placed in a sintering furnace for sintering. The sintering method is vacuum-gas pressure sintering. The temperature is raised by program. The heating rate is 10 °C / min. The vacuum sintering is performed to 1200 °C. The vacuum sintering pressure is 0.05 Pa. After 1200 °C, it is switched to gas pressure sintering. The gas pressure sintering pressure is 11 MPa. The maximum sintering temperature is 1450 °C. The holding time is 3 h. After the high-temperature sintering is completed, the titanium carbonitride-based metal ceramic material is obtained by cooling.

[0059] Performance test results: flexural strength is 2290MPa, fracture toughness is 11.8MPa·m 1 / 2 After quenching at 700℃, the strength is 1820MPa, and the unit area oxidation weight gain is 6×10 -4 mg / mm 2 .

[0060] Example 3

[0061] Raw materials: WC 18%; Mo2C 7%; TaC and NbC 2% (TaC and NbC mass ratio 1:1); Nickel and Cobalt 25% (Ni / Co mass ratio 6:4); NbN and AlN 1.0% (NbN and AlN mass ratio 3:7); Si3N4 whisker 0.5%; Zr 1.0%; Carbon black 0.6%; The balance is Ti (C, N), measured based on the total mass as 100%.

[0062] (1) Pretreatment of Si3N4 whiskers: After degreasing and cleaning, a nickel coating is plated on the surface of the Si3N4 whiskers by chemical plating. The nickel particles in the nickel coating have a size range of 40 to 60 nm and a nickel plating thickness of about 400 nm.

[0063] (2) Powder premixing: The metal binder phase (Co and Ni) and Zr and C are carbon oxidized by high-energy ball milling. The high-energy reaction ball milling method is dry milling. The ball milling speed is 450 r / min, the ball-to-material ratio is 12:1, the ball milling time is 3 h, and the ball milling atmosphere is argon atmosphere with an oxygen content of 1.0 vol.%. After high-energy ball milling, they are premixed with nitride powders such as NbN and AlN by ordinary ball milling. The ordinary ball milling premixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 180 r / min, the ball-to-material ratio is 4:1, and the ball milling time is 30 h to obtain a binder phase premixed powder.

[0064] (3) Mixing of raw powders: The premixed powder of the binder phase, Ti(C,N), WC, Mo2C, TaC and NbC, and a molding agent (paraffin wax, added in an amount of 0.4% of the total mass of the powder) are mixed by ordinary ball milling. The mixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 180 r / min, the material ratio is 4:1, and the ball milling time is 30 h. Then, Si3N4 whiskers with nickel plating on the surface are added and continued to be mixed by low-intensity ball milling. The low-intensity ball milling adopts wet ball milling. The ball milling medium is alcohol. Roller ball milling is used. The ball milling speed is 60 r / min, the material ratio is 1.5:1, and the grinding time is 8 h. The mixed material is obtained after drying.

[0065] (4) Pressing and sintering: The mixture is pressed under certain conditions. The pressing adopts die pressing with a pressing pressure of 180 MPa to obtain a pressed blank. The pressed blank is placed in a sintering furnace for sintering. The sintering adopts a vacuum-gas pressure sintering method. The temperature is raised by programmed sintering with a heating rate of 8°C / min. The mixture is vacuum sintered to 1200°C with a vacuum sintering pressure of 0.5 Pa. After 1200°C, it is switched to gas pressure sintering with a gas pressure sintering pressure of 8 MPa, a maximum sintering temperature of 1500°C, and a holding time of 2 h. After high-temperature sintering, the mixture is cooled to obtain a titanium carbonitride-based metal ceramic material.

[0066] Performance test results: flexural strength is 2600MPa, fracture toughness is 13MPa·m 1 / 2 After quenching at 700℃, the strength is 2200MPa, and the unit area oxidation weight gain is 2.2×10 -4 mg / mm 2 .

[0067] Example 4

[0068] Raw materials: WC 20%; Mo2C 8%; TaC and NbC 1% (TaC and NbC mass ratio 1:1); Nickel and cobalt 25% (nickel and cobalt mass ratio 5:5); NbN and AlN 1.0% (NbN and AlN mass ratio 3:7); Si3N4 whisker 0.5%; Zr 2.0%; carbon black 1.0%; the balance is Ti (C, N), measured based on the total mass as 100%.

[0069] (1) Pretreatment of Si3N4 whiskers: After degreasing and cleaning, a nickel coating is plated on the surface of the Si3N4 whiskers by chemical plating. The nickel particles in the nickel coating have a size range of 60 to 80 nm and a nickel plating thickness of about 450 nm.

[0070] (2) Powder premixing: The metal binder phase (Co and Ni) and Zr and C are carbon oxidized by high-energy ball milling. The high-energy reaction ball milling method is dry milling. The ball milling speed is 450 r / min, the ball-to-material ratio is 13:1, the ball milling time is 3 h, the ball milling atmosphere is argon atmosphere, and the oxygen content is 1.5 vol.%. After high-energy ball milling, they are premixed with nitride powders such as NbN and AlN by ordinary ball milling. The ordinary ball milling premixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 180 r / min, the ball-to-material ratio is 5:1, and the ball milling time is 26 h to obtain a binder phase premixed powder.

[0071] (3) Mixing of raw powders: The binder phase premixed powder, Ti(C,N), WC, Mo2C, TaC, NbC, and a molding agent (paraffin wax, added in an amount of 0.5% of the total mass of the powder) are mixed by ordinary ball milling. The mixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 180 r / min, the material ratio is 5:1, and the ball milling time is 26 h. Then, Si3N4 whiskers with nickel plating on the surface are added and continued to be mixed by low-intensity ball milling. The low-intensity ball milling adopts wet ball milling. The ball milling medium is alcohol (industrial anhydrous ethanol). Roller ball milling is used. The material ratio is 1:1, the ball milling speed is 60 r / min, and the milling time is 10 h. The mixed material is obtained after drying.

[0072] (4) Pressing and sintering: The mixture is pressed and formed under certain conditions. The pressing adopts die pressing and the pressing pressure is 160 MPa to obtain a pressed blank. The pressed blank is placed in a sintering furnace for sintering. The sintering adopts a vacuum-gas pressure sintering method. The temperature is raised by programmed sintering at a rate of 8 °C / min. The mixture is vacuum sintered to 1200 °C and the vacuum sintering pressure is 1 Pa. After 1200 °C, it is switched to gas pressure sintering. The gas pressure sintering pressure is 10 MPa, the maximum sintering temperature is 1460 °C, and the holding time is 1.5 h. After the high-temperature sintering is completed, the mixture is cooled to obtain a titanium carbonitride-based metal ceramic material.

[0073] Performance test results: flexural strength is 2460MPa, fracture toughness is 12MPa·m 1 / 2 After quenching at 700℃, the strength is 1840MPa, and the unit area oxidation weight gain is 6×10 -4 mg / mm 2 .

[0074] Example 5

[0075] Raw materials: WC 18%; Mo2C 5%; TaC and NbC 1% (TaC and NbC mass ratio 1:1); Nickel and Cobalt 21% (Ni / Co mass ratio 5:5); NbN and AlN 0.4% (NbN and AlN mass ratio 3:7); Si3N4 whisker 0.8%; Zr 1.0%; Carbon black 0.5%; The balance is Ti (C, N), measured based on the total mass as 100%.

[0076] (1) Pretreatment of Si3N4 whiskers: After degreasing and cleaning, a nickel coating is plated on the surface of the Si3N4 whiskers by chemical plating. The nickel particles in the nickel coating have a size of less than 100 nm and a nickel plating thickness of about 350 nm.

[0077] (2) Powder premixing: The metal binder phase (Co and Ni) and Zr and C are carbon oxidized by high-energy ball milling. The high-energy reaction ball milling method is dry milling. The ball milling speed is 400 r / min, the ball-to-material ratio is 15:1, the ball milling time is 4 h, the ball milling atmosphere is argon atmosphere, and the oxygen content is 1.8 vol.%. After high-energy ball milling, they are premixed with nitride powders such as NbN and AlN by ordinary ball milling. The ordinary ball milling premixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 180 r / min, the ball-to-material ratio is 6:1, and the ball milling time is 24 h to obtain a binder phase premixed powder.

[0078] (3) Mixing of raw powders: The premixed powder of the binder phase, Ti(C,N), WC, Mo2C, TaC, NbC and a molding agent (paraffin wax, added in an amount of 0.4% of the total mass of the powder) are mixed by ordinary ball milling. The mixing method is wet milling. The ball milling medium is alcohol (industrial anhydrous ethanol). The ball milling speed is 180 r / min, the material ratio is 3:1, and the ball milling time is 24 h. Then, Si3N4 whiskers with nickel plating on the surface are added and continued to be mixed by low-intensity ball milling. The low-intensity ball milling adopts wet ball milling. The ball milling medium is alcohol (industrial anhydrous ethanol). Roller ball milling is used. The material ratio is 2:1, the ball milling speed is 60 r / min, and the milling time is 6 h. The mixed material is obtained after drying.

[0079] (4) Pressing and sintering: The mixture is pressed and formed under certain conditions. The pressing adopts mold pressing and the pressing pressure is 150 MPa to obtain a pressed blank. The pressed blank is placed in a sintering furnace for sintering. The sintering adopts a vacuum-gas pressure sintering method. The sintering is performed by programmed temperature rise. The heating rate is 8°C / min. Before the sintering temperature is 1200°C, the sintering platforms are 120°C, 400°C, 800°C, and 1000°C. The holding time is 60 minutes. The mixture is vacuum sintered to 1200°C and the vacuum sintering pressure is 0.09 Pa. After 1200°C, it is switched to gas pressure sintering. The gas pressure sintering pressure is 6 MPa, the maximum sintering temperature is 1550°C, and the holding time is 1 hour. After the high-temperature sintering is completed, the mixture is cooled to obtain a titanium carbonitride-based metal ceramic material.

[0080] Performance test results: flexural strength is 2350MPa, fracture toughness is 12.5MPa·m 1 / 2 After quenching at 700℃, the strength is 1760MPa, and the unit area oxidation weight gain is 5×10 -4 mg / mm 2 .

[0081] Comparative Example 1

[0082] Compared with Example 3, the only difference is that the raw materials are different.

[0083] Raw materials: WC 18%; Mo2C 7%; TaC and NbC 2% (TaC and NbC mass ratio 1:1); Nickel and Cobalt 14% (Ni-Co mass ratio 6:4); NbN and AlN 1.0% (NbN and AlN mass ratio 3:7); Si3N4 whisker 0.5%; Zr 1.0%; Carbon black 0.6%; The balance is Ti (C, N), measured based on the total mass as 100%.

[0084] Performance test results: flexural strength 1630MPa, fracture toughness 7.3MPa·m 1 / 2 After quenching at 700℃, the strength is 1160MPa, and the unit area oxidation weight gain is 6×10-4 mg / mm 2 .

[0085] Comparative Example 2

[0086] Compared with Example 3, the only difference is that the raw materials are different.

[0087] Raw materials: WC 18%; Mo2C 7%; TaC and NbC 2% (TaC and NbC mass ratio 1:1); Nickel and Cobalt 25% (Ni:Co mass ratio 6:4); NbN and AlN 1.0% (NbN and AlN mass ratio 3:7); Zr 1.0%; Carbon black 0.6%; The balance is Ti (C, N), measured based on the total mass as 100%.

[0088] Performance test results: flexural strength 1840MPa, fracture toughness 6.8MPa·m 1 / 2 After quenching at 700℃, the strength is 1520MPa, and the unit area oxidation weight gain is 2.4×10 -4 mg / mm 2 .

[0089] Comparative Example 3

[0090] Compared with Example 3, the only difference is that the raw materials are different.

[0091] Raw materials: WC 18%; Mo2C 7%; TaC and NbC 2% (TaC and NbC mass ratio 1:1); Nickel and Cobalt 25% (Ni / Co mass ratio 6:4); NbN and AlN 0.1% (NbN and AlN mass ratio 3:7); Si3N4 whisker 0.5%; Zr 1.0%; Carbon black 0.6%; The balance is Ti (C, N), measured based on the total mass as 100%.

[0092] Performance test results: flexural strength is 2190MPa, fracture toughness is 10MPa·m 1 / 2 After quenching at 700℃, the strength is 1720MPa, and the unit area oxidation weight gain at 800℃ within 10h is 3.2×10 -4 mg / mm 2 .

[0093] Comparative Example 4

[0094] The only difference compared with Example 3 is that the Si3N4 whiskers are not subjected to nickel plating.

[0095] Performance test results: flexural strength is 1990MPa, fracture toughness is 7.1MPa·m 1 / 2 After quenching at 700℃, the strength is 1610MPa, and the unit area oxidation weight gain is 2.6×10-4 mg / mm 2 。

Claims

1. A titanium carbonitride-based cermet material, characterized in that: The titanium carbonitride-based cermet material comprises a nickel-cobalt metal bonding phase, a zirconium oxide dispersion phase and a silicon nitride whisker reinforcement phase; The titanium carbonitride-based metal ceramic material is obtained from powder raw materials by a powder metallurgy method; the raw materials are composed of the following mass percentage components: WC 15-20%; Mo2C 5-8%; TaC and / or NbC 1-3%; Ni and Co20-25%; NbN and / or AlN 0.2-1.0%; Si3N4 whisker 0.5-1.0%; Zr1.0-3.0%; carbon black 0.4-1.0%; the balance is Ti (C, N); The titanium carbonitride-based metal ceramic material is obtained by the following preparation method: comprising the following steps: 1) cleaning and nickel-plating the surface of Si3N4 whiskers to obtain nickel-plated Si3N4 whiskers; 2) After carbon oxidation of Zr, carbon black, Co and Ni powders by high-energy ball milling, the powders are mixed with NbN and / or AlN powders by ball milling I to obtain mixed powder I, the mixed powder I is mixed with Ti(C,N), WC, Mo2C and TaC and / or NbC powders by ball milling II to obtain mixed powder II, the mixed powder II is mixed with nickel-plated Si3N4 whiskers by ball milling III, and then dried to obtain mixed powder III; the purpose of the carbon oxidation is to form finely dispersed zirconium oxide and zirconium carbide in the metal phase; 3) The mixed powder III is pressed and sintered to obtain a titanium carbonitride-based metal ceramic material.

2. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The particle size of the Ti(C,N) is 4-6 μm; The particle sizes of WC, Mo2C, TaC, NbC, Zr, carbon black, NbN, AlN, Co and Ni are all 3-8 μm; The silicon nitride whisker has a diameter of 0.5-1.0 μm and a length of 20-50 μm.

3. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The nickel particles in the nickel coating on the surface of the nickel-plated Si3N4 whisker have a particle size of less than 100 nm, and the thickness of the nickel coating is 300-500 nm.

4. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The conditions of the high-energy ball milling are: dry ball milling, a ball milling speed of 400-500 r / min, a ball-to-material ratio of (10-15):1, a ball milling time of 2-4 h, and an inert atmosphere with an oxygen content of less than 2 vol. %.

5. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The conditions of the ball milling mixing I are: wet ball milling, alcohol as the ball milling medium, a ball milling speed of 150-200 r / min, a ball to material ratio of (3-6):1, and a ball milling time of 24-48 h; The conditions of the ball milling mixing II are: wet ball milling, alcohol as the ball milling medium, a ball milling speed of 150-200 r / min, a ball to material ratio of (3-6):1, and a ball milling time of 24-48 h; The conditions of the ball milling mixing III are: wet ball milling, the ball milling method is planetary ball milling or drum ball milling; when planetary ball milling is used, the ball milling medium is alcohol, the ball milling speed is 100-120 r / min, the ball-to-material ratio is (1-2):1, and the ball milling time is 3-6 h; when drum ball milling is used, the ball milling speed is 50-80 r / min, and the ball milling time is 6-12 h.

6. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The compression molding is performed by die pressing or cold isostatic pressing, and the compression molding pressure is 150-200 MPa.

7. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The sintering adopts a vacuum-gas pressure sintering method, and the sintering is carried out by programmed temperature rise, with a heating rate of 5~10℃ / min, first vacuum sintering to 1200℃, and the vacuum sintering gas pressure is 0.01~1 Pa; after 1200℃, it is switched to gas pressure sintering, the gas pressure sintering pressure is 5~11MPa, the maximum sintering temperature is 1450℃~1550℃, and the insulation time is 1~3h.

Citation Information

Patent Citations

  • Titanium carbonitride cermet material for wire drawing die and preparation method

    CN111500949A

  • Ti (C, N)-based metal ceramic cutter material containing AlN and TiB2 and preparation method of Ti (C, N)-based metal ceramic cutter material

    CN115369300A

  • Cutting tool made of titanium carbonitride-base cermet excellent in wear resistance and breakage resistance

    JP1994172910A